Sistem Informasi Badan Penjaminan Mutu STMIK Bina Mulia Palu Berbasis Web - Fitriyanti Andi Masse; Andi Rusdin Palawagau; Yerry Cristian Wenas (Jurnal Elektronik Sistem Informasi dan Komputer, 2025)
Technology developments are currently increasing rapidly, starting from home appliances technology, clothes, networks, especially websites. Every office and university has a website as a tool to exchange information and to complete work anywhere without meeting in person. This research aims to create a Web-Based Quality Assurance Agency Information System so that archiving, data searching, and data access can be done anywhere and anytime. This research is a qualitative research. This research was conducted at STMIK Bina Mulia Palu for 3 months starting from September to November 2023. Data was collected through observation, interview, and literature review. This research use primary and secondary data. From the results of research and system design, this website can be built with the aim of helping users to obtain the information about STMIK Bina Mulia Palu wherever and whenever.